Filem sebagai media pengajaran Kor-sispa di universiti awam / Che Zuina Ismail ... [et al.] - Ismail, Che Zuina; Wan Abdul Aziz, Wan Asri; Mohd Zulkipli, Mohd Faizul Idham; Che Mat, Azman (2018)
Kor-Sispa is a uniform body under the Malaysian Civil Defense Force (APM) formerly known as JPAM. It is an important organization in Malaysia. This paper presents some issues such as soft skills as the co-curricular objectives of the university, the role of Kor-sispa unit and teaching innovation with the use of film as a media in teaching and learning (TL). This paper discusses the use of media, which is film/video clips as a method of Kor-sispa teaching. The question is whether this method suitable for use based on objective background, syllabus and the use of film/video clips in the field of TL across multiple disciplines. TL activities that fit the subject presentation could have a better effect. Media usage is one way to enrich the TL process. Finally, this paper proposes a field study to evaluate, measure and formulate the acceptance of film as a TL innovation in the Kor-sispa unit.